1977
DOI: 10.1073/pnas.74.5.1879
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of histone H1 in the organization of the chromosome fiber.

Abstract: ABSTRACTnaked DNA, and that it is the cooperative binding of histone Hi that is responsible for the folding of the thin chromosome fiber. The results of four independent experimental approaches provide evidence that supports this view: (i) competition between long and short nucleosome chains for histone Hi analyzed by filter binding; (ii) the distribution of histone Hi in mixtures of long and short chromosome fibers separated by sucrose gradient velocity sedimentation; (iii) the sedimentation behavior of long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(132 citation statements)
references
References 24 publications
10
122
0
Order By: Relevance
“…Furthermore, it was not possible to investigate the effects of chromatin concentration and sedimentation coefficients have not, therefore, been corrected for this parameter. Analysis was carried out in a buffer containing 80 mM NaCI, which provided the conditions necessary to induce higher order folding of the chromatin (3,9,30,36) . A summary of the results of this study are shown in Fig .…”
Section: Sedimentationmentioning
confidence: 99%
“…Furthermore, it was not possible to investigate the effects of chromatin concentration and sedimentation coefficients have not, therefore, been corrected for this parameter. Analysis was carried out in a buffer containing 80 mM NaCI, which provided the conditions necessary to induce higher order folding of the chromatin (3,9,30,36) . A summary of the results of this study are shown in Fig .…”
Section: Sedimentationmentioning
confidence: 99%
“…A possible approach to the detection of critical sites of DNA modification in the mammalian genome may be to study the mode of distribution of specific carcinogen-DNA adducts in relation to defined chromatin fractions, e.g., in the DNA of actively transcribed versus inactive chromatin and/or chromatin of various folding levels. While the precise structure of transcriptionally active chromatin is still unclear, chromatin is now generally accepted to be organized in the form of condensed, 20-30 nm thick fibers (Finch and Klug, 1976;Renz et al, 1977), representing the next higher folding level of the 11 nm thick nucleosomal fiber (Kornberg, 1977). We have previously shown that in rat brain chromatin briefly exposed to the ethylating N-nitroso carcinogen, N-ethyl-N-nitrosourea (Et-NU) in vitro, the alkylation product 06-ethyl-2'-deoxyguanosine (O6-EtdGuo) is formed at a lower rate in the DNA IRL Press Limited, Oxford, England.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the solenoid model suggests the cooperative mode. Some authors have suggested the non-cooperative mode [4,5] to be the correct description, whereas the cooperative form [6,7] was proposed by others. Chromatin samples of less than 30 nucleosomes in length, often shorter than dodecamers, were used in these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the mode of interaction between chromatin and linker histone would reduce the possibility of higher order structures of chromatin. However, the reported results would still require clarification; some workers have suggested a noncooperative mode [4,5] while others have proposed a cooperative type [6,7].…”
Section: Introductionmentioning
confidence: 99%